An analytical model for mixing based on time-interleaved sequential segmentation - Nguyen, Nam-Trung (2012)
Due to constrains caused by the laminar flow in microscale, effective and fast mixing is important for many microfluidic applications. From the scaling law, decreasing the mixing path can shorten the mixing time and enhance the mixing quality. One of the techniques for reducing mixing path is time-interleaved sequential segmentation. This technique divides solvent and solute into segments in axial direction. The mixing path can be controlled by the switching frequency and the mean velocity of the flow. In this brief communication, we present a simple time-dependent one-dimensional analytical model for time-interleaved sequential segmentation. The model considers an arbitrary mixing ratio between solute and solvent as well as the axial Taylor–Aris dispersion. The analytical solution indicates that the Peclet number is the key parameter for this mixing concept.